Hookworm Infection and its Problems in Central Java - Ag. Soemantri; Harsoyo N. (Indonesian Pediatric Society, 1983)
The correlation of worm load, haemoglobin level and the nutritional status in children who had hookworm infection were estimated. The iron deficiency anaemia in the school age children was caused by hookworm infection. The worse the nutritional status of the child, the lower was the haemoglobin level. Besides anthelmintics treatment and the iron supplementation, primary health care education was also given simultaneously.